Investigating the effect of large solar flares on the ionosphere based on novel Digisonde data comparing three different methods - Buzás, Attila; Kouba, Daniel; Mielich, Jens; Burešová, Dalia; Mošna, Zbyšek; Koucká Knížová, Petra; Barta, Veronika (Frontiers in Astronomy and Space Sciences, 2023)
Increased solar radiation during solar flare events can cause additional ionization and enhanced absorption of the electromagnetic (EM) waves in the ionosphere leading to partial or even total radio fade-outs. In this study, the ionospheric response to large solar flares has been investigated using the ionosonde data from Juliusruh (54.63° N, 13.37° E), Průhonice (49.98° N, 14.55° E) and San Vito (40.6° N, 17.8° E) Digisonde (DPS-4D) stations. We studied the effect of 13 intense (>C4.8) solar flares that occurred between 06:00 and 16:30 (UT, daytime LT=UT+1 h) from 04-10 September 2017 using three different methods. A novel method based on the amplitude data of the measured EM waves is used to calculate and investigate the relative absorption changes (compared to quiet period) occurring during the flares. The amplitude data are compared with the variation of the fmin parameter (fmin, the minimum measured frequency, it is considered as a qualitative proxy for the "nondeviative" radio wave absorption). Furthermore, the signal-to-noise ratio (SNR) measured by the Digisondes was used as well to quantify and characterize the fade-out events and the ionospheric absorption. In order to compare the three different methods, residuals have been defined for all parameters, which provide the percentage changes compared to the selected reference periods. Total and partial radio fade-outs, increased values (+0.4-318%) of the fmin parameter, and +20-1400% amplitude changes (measured at 2.5 and 4 MHz) were experienced during and after the investigated flares. Generally, the observed changes depended on the intensity, solar zenith angle and duration of the flare events. Although the three different methods have their own advantages/disadvantages and their limitations, the combination of them seems to be an efficient approach to monitor the ionospheric response to solar flares.